Information sources and investment decision among Malaysian investors: Clarifying the role of gender and product knowledge - Yusuff, Noraini; Mansor, Fadillah; Ahmad Musadik, Siti Hajar Salwa; Abu Bakar, Azizi; Omar, Hydzulkifli Hashim (Advance Scientific Research, 2020)
This study explore the moderation effect of gender and product knowledge (PK) on the relationship between information sources (IS) and Islamic unit trust investment decision (IUTID). Muslim investors in Malaysia was chosen as the respondents for this study. The relationship between the variable was tested using Partial Least Square Structural Equation Modelling (PLS-SEM). Our results show that both variables, gender and product knowledge moderate the relationship between information sources and Islamic unit trust investment decision. The result indicate that information sources strongly influence Islamic unit trust investment decision when the Muslim investors have low product knowledge. In addition, the finding also reveal that information sources strongly influence Islamic unit trust investment decision more for female investors than male investors.